The Implementation of Home Room Technique through Group Guidance Services in Gaining Students’ Self-confidence - Sulfian Syarif (Universitas Muhammadiyah Barru, 2021)
This study aimed at elaborating the home room technique model through group guidance services and describing the role of the home room technique in gaining students' self-confidence. This research is descriptive qualitative design. The subjects of this study were ten students of class III-IPA at SMA Muhammadiyah Kalosi, Enrekang Regency. The researcher collected the data based on the result of observation, interview, and document review. The result of the current research indicated that student self-confidence increases after they are treated with the implementation of group guidance service using the home room technique.